DETECTING FAKE ACCOUNT ON SOCIAL MEDIA USING MACHINE LEARNING ALGORITHMS - Dr.K.Sreenivasa Rao, Dr.G.Sreeram, DR. B.DEEVENA RAJU (International Journal of Control and Automation, 2020)
In the present generation, On-Line social networks (OSNs) have become increasingly popular, which impacts people's social lives and impel them to become associated with various social media sites [1].  Social Networks are the essential platforms through which many activities such as promotion, communications, agenda creation, advertisements, and news creation have started to be done. Adding new friends and keeping in contact with them and their updates has become easier. Researchers have been studying these online social networks to see the impact they make on the people. Some malicious accounts are used for purposes such as misinformation and agenda creation. Detection of malicious account is significant. The methods based on machine learning-based were used to detect fake accounts that could mislead people. The dataset is pre-processed using various python libraries and a comparison model is obtained to get a feasible algorithm suitable for the given dataset [2]. An attempt to detect fake accounts on the social media platforms is determined by various Machine Learning algorithms. The classification performances of the algorithms Random Forest, Neural Network and Support Vector Machines are used for the detection of fake accounts.